Variation in fibre properties of wood under Malaysian dipterocarpaceae / Suhaimi Muhammed - Muhammed, Suhaimi (2006)
Four wood species belonging to Malaysian dipterocarpaceae namely engkabang, keladan giam kancing and sengkawang air were selected for this study. Wood samples taken from three trees, five segments, two radii and four height levels were used in determining fibre properties such as fibre length, fibre diameter, lumen width and cell wall thickness. The objectives were to determine the extent of among tree, radial and vertical variation of the said properties. Among tree variation was significant for fibre diameter, lumen width and cell wall thickness in keladan and fibre length, fibre diameter and lumen width exhibited significant variation in sengkawang air. Radial variation along the radii and segments were highly significant for almost all the fibre properties in the four wood species but vertical variation along different height levels of the tree was not significant, although slight vatiation existed for individual cases. The finding revealed that segment number from the pith greatly influences the fibre properties of all the four wood species studied. This implies the possibility of improving the wood quality of these dipterocarp species through the manipulation of rotation age.